2008
DOI: 10.1007/s10190-008-0008-5
|View full text |Cite
|
Sign up to set email alerts
|

Contamination microbiologique résiduelle des endoscopes digestifs

Abstract: Les endoscopes sont des dispositifs médicaux qui ne peuvent faire l'objet de mesures de stérilisation en raison de leur caractère complexe et notamment de la sensibilité à la chaleur de certains de leurs constituants. La complexité de leur structure rend possible une accumulation de souillures organiques ou minérales qui peuvent elles-mêmes renfermer des agents infectieux. Une fré-quence ou une qualité insuffisante de la procédure de désinfection peut aboutir à la formation d'un biofilm.L'objectif de notre tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
1
Order By: Relevance
“…The study conducted at the CHU de Fés (Morocco) showed the presence of other organisms such as Acinetobacter baumanni, Escherichia sp, and Candida sp [9]. This is not the case in this study.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The study conducted at the CHU de Fés (Morocco) showed the presence of other organisms such as Acinetobacter baumanni, Escherichia sp, and Candida sp [9]. This is not the case in this study.…”
Section: Discussioncontrasting
confidence: 69%
“…The drying step must be rigorous especially in the channels to avoid the progressive installation of a biofilm, which could explain the presence of Pseudomonas aeruginosa in the channels of the endoscopes studied [9].…”
Section: Discussionmentioning
confidence: 99%